Distribuição longitudinal, ocupação ambiental, alimentação e época reprodutiva de quatro espécies de Cyprinodontiformes (Osteichthyes) coexistentes no rio Ubatiba (Maricá, RJ) - Aranha, José Marcelo Rocha (1991)
Aspects of biology of Phalloceros caudimaculatus (Hensel, 1868); Poecilia vivipara Bloch & Schneider, 1801; Phalloptychus Januarius (Hensel, 1868 ) and Jenynsia lineata (Jenyns, 1842) were analysed through monthly captures at four sites along the Ubatiba River and one site in the Maricá Lagoon, the State of Rio de Janeiro, Brazil (22° 55'S/42° 49'W). The collections in the Ubatiba river shown that P. caudimaculatus was preferably present in the upper section of the stream; P. vivipara occurred in the medium and lower sections; P. januarius and J. lineata occurred only in the lower sections. The species ocurred in adjacent puddles and the shore In the lower with vegetations in the upper and medium sections. one, the fishes occupied the shores and the bed of the river. The influence of abiotic (e.g , velocity and transparency of water) and biotic factors (competition and predation) in the environmental occupation by the four species is discussed. The alimentary circadian rythms was analysed for the four species and shown , essentially , daily activity with two a matinal and an evening peaks. P. caudimaculatus shown a peaks: longer period of activity than the others species studied. The reproduction did not show any seasonal pattern. The diet was basically herbivore for all four species and along the stream. However, in one of the collection sites the principal item was chironomid larvae related, probably, with the little availability of algae in the environment. Intra and interspecific differences in the diet were found between P. Januarius and J. lineata.